Culture and management control interdependence: An analysis of control choices that complement the delegation of authority in Western cultural regions - Malmi, Teemu; Bedford, David S.; Brühl, Rolf; Dergård, Johan; Hoozée, Sophie; Janschek, Otto; Willert, Jeanette; Ax, Christian; Bednarek, Piotr; Gosselin, Maurice; Hanzlick, Michael; Israelsen, Poul; et al. (Accounting, Organizations and Society, 2020)
This study examines the influence of cultural regions on the interdependence between delegation of authority and other management control (MC) practices. In particular, we assess whether one of the central contentions of agency theory, that incentive contracting and delegation are jointly determined, holds in different cultural regions. Drawing on prior literature, we hypothesise that the MC practices that operate as a complement to delegation vary depending on societal values and preferences, and that MC practices other than incentive contracting will complement delegation in firms in non-Anglo cultural regions. Using data collected from 584 strategic business units across three Western cultural regions (Anglo, Germanic, Nordic), our results show that the interdependence between delegation and incentive contracting is confined to Anglo firms. In the Nordic and Germanic regions, we find that strategic and action planning participation operate as a complement to delegation, while delegation is also complemented by manager selection in Nordic firms. Overall, our study demonstrates that cultural values and preferences significantly influence MC interdependence, and suggests that caution needs to be taken in making cross-cultural generalisations about the complementarity of MC practices.